Implementasi Pembelajaran Pendidikan Agama Islam (PAI) dalam Membentuk Karakter Siswa di SMP Negeri 3 Tanjung Pura Langkat - Selamat; Munawir Pasaribu; Sofyan (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2025)
This study aims to analyze the implementation of Islamic Religious Education (PAI) learning at SMP Negeri 3 Tanjung Pura Langkat and its impact on shaping students' character. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that the PAI learning process at SMP Negeri 3 is designed with a focus on character development, integrating values ​​such as honesty, responsibility, discipline, and tolerance. The implementation of learning is carried out using various methods, such as congregational prayer, short lectures, group discussions, and educational games. Evaluation is carried out through continuous assessment of students' academic and behavioral development, including daily observations and attitude assessments. This study concludes that PAI learning at SMP Negeri 3 has succeeded in making a positive contribution to the development of students' character, and the results can be a reference for other schools in implementing effective PAI programs. This study emphasizes the importance of cooperation in achieving optimal student character development through PAI.